2008
DOI: 10.1371/journal.pmed.0050225
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mental Disorders among the Homeless in Western Countries: Systematic Review and Meta-Regression Analysis

Abstract: BackgroundThere are well over a million homeless people in Western Europe and North America, but reliable estimates of the prevalence of major mental disorders among this population are lacking. We undertook a systematic review of surveys of such disorders in homeless people.Methods and FindingsWe searched for surveys of the prevalence of psychotic illness, major depression, alcohol and drug dependence, and personality disorder that were based on interviews of samples of unselected homeless people. We searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
671
10
48

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 853 publications
(802 citation statements)
references
References 67 publications
40
671
10
48
Order By: Relevance
“…[4][5][6][7][8][9] Furthermore, individual-level studies that focus on people who are living on the street, living in areas not meant for human habitation, or accessing emergency or transitional housing services have consistently found elevated rates of alcohol use and problems among the homeless. [10][11][12][13][14][15] While important, homelessness is the most extreme form of a much larger continuum of housing instability. 16 Data from the Michigan Recession and Recovery Study (MRRS) indicate that while 29.6 % of individuals living in Southeastern Michigan experienced some form of housing instability between 2007 and 2009, only 2.1 % reported homelessness in the past 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Furthermore, individual-level studies that focus on people who are living on the street, living in areas not meant for human habitation, or accessing emergency or transitional housing services have consistently found elevated rates of alcohol use and problems among the homeless. [10][11][12][13][14][15] While important, homelessness is the most extreme form of a much larger continuum of housing instability. 16 Data from the Michigan Recession and Recovery Study (MRRS) indicate that while 29.6 % of individuals living in Southeastern Michigan experienced some form of housing instability between 2007 and 2009, only 2.1 % reported homelessness in the past 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…3 People who are homeless suffer considerably worse health than the general population, 4 contributing to an age-standardized mortality rate up to four times higher among this group. 5,6 Mental disorders are prevalent among homeless people, [7][8][9] with substance dependence the most common diagnosis among homeless populations across the Western world, occurring at rates far exceeding those among the general population. [10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug. 7 Other evidence suggests that more than half of homeless people with a substance use disorder suffer at least one comorbid psychiatric disorder. 14 Substance use disorders are commonly considered to be associated with the etiology of homelessness, a notion captured in the 'social selection' model and underpinned by the proposition that homelessness represents the endpoint of the gradual depletion of an individual's economic and social resources as a result of their substance dependence.…”
Section: Introductionmentioning
confidence: 99%
“…The average age at death among this group is estimated to be 42 to 52 years, with 30% to 70% of deaths related to alcohol abuse (IshorstWitte et al, 2001;Larimer, 2009;O'Connell, 2005. A meta-analysis of 29 studies on mental disorders among homeless people by Fazel et al (2008) reported that the most common disorders among this group were alcohol dependence (8.1%-58.5%), drug dependence (4.5%-54.2%), psychotic illness (2.8%-42.3%), and major depression (0%-41%).…”
Section: Problem Gambling and Homelessness In Contextmentioning
confidence: 99%